Association of time to diagnosis with socioeconomic position and geographical accessibility to healthcare among symptomatic COVID-19 patients: A retrospective study in Hong Kong. (November 2020) - Wu, Yushan; Yan, Xiang; Zhao, Shi; Wang, Jingxuan; Ran, Jinjun; Dong, Dong; Wang, Maggie; Fung, Hong; Yeoh, Eng-kiong; Chung, Roger Yat-Nork
Abstract: Early diagnosis is important to control COVID-19 outbreaks. This study aimed to assess how individual and area socioeconomic position and geographical accessibility to healthcare services were associated with the time to diagnosis among symptomatic COVID-19 patients in Hong Kong. Multivariable generalized linear regression was used to estimate the associations while adjusting for sociodemographic characteristics and case classification. This study found living in public rental housing and living in an area with low education were associated with longer time to diagnosis in the first wave of infections. Specifically, the risk of delayed diagnosis for public rental housing residents was mitigated by the higher density of public clinics/hospitals but was slightly increased by the higher density of private medical practitioners nearby. No such relations were found in the second wave of infections when the surveillance measures were enhanced. Given the grave impact of pandemics around the world, our findings call on taking inequalities into account when public health policies are being devised. Highlights: Early diagnosis of COVID-19 is vital to break the transmission chain and save lives. Research on inequality in time to diagnosis of emerging infectious disease is scant. Socioeconomic inequality was observed in time to diagnosis of COVID-19 in Hong Kong. Better spatial access to public health care mitigated the risk of delayed diagnosis. Inequality disappeared when surveillance measures strengthened.